Consecutive hydrazino-Ugi-azide reactions: synthesis of acylhydrazines bearing 1,5-disubstituted tetrazoles - Barreto, Angélica de Fátima S.; Santos, Veronica Alves dos; Andrade, Carlos Kleber Z. (Beilstein Journal of Organic Chemistry, 2017)
Isocyanide-based multicomponent reactions (IMCRs) allow the construction of relatively complex molecules through a one-pot synthesis. The combination of IMCRs in a consecutive or sequential fashion further extends the complexity of the molecules obtained. Herein, we report the efficient application of this approach to the synthesis of acylhydrazines bearing 1,5-disubstituted tetrazoles. Our strategy was accomplished in only three steps: first, a one-pot hydrazino-Ugi-azide four-component reaction; second a hydrazinolysis and finally an additional hydrazino-Ugi-azide reaction. This sequence provides the title compounds in moderate to excellent yields. The products synthesized herein contain functional groups within their structures that can be easily modified to obtain new acylhydrazino 1,5-disubstituted tetrazoles.
Keywords: acylhydrazines; consecutive Ugi reactions; 1,5-disubstituted tetrazoles; isocyanide-based multicomponent reactions (IMCRs); Ugi-azide reaction